Twilight of the republic : empire and exceptionalism in the American political tradition - Litke, Justin B., 1984- (University Press of Kentucky, 2013)
The uniqueness of America has been alternately celebrated and panned, emphasized and denied, for most of the country's history -- both by its own people and by visitors and observers from around the world. The idea of ""American exceptionalism"" tends to provoke strong feelings, but few are aware of the term's origins or understand its true meaning. Understanding the roots and consequences of America's uniqueness requires a thorough look into the nation's history and Americans' ideas about themselves. Through a masterful analysis of important texts and key documents, Justin B. Litke i